2006
DOI: 10.1186/1471-2296-7-47
|View full text |Cite
|
Sign up to set email alerts
|

German ambulatory care physicians' perspectives on clinical guidelines – a national survey

Abstract: BackgroundThere has been little systematic research about the extent to which German physicians accept or reject the concept and practice ofa) clinical practice guidelines (CPG) andb) evidence based medicine (EBM)The aim of this study was to investigate German office-based physicians' perspective on CPGs and EBM and their application in medical practice.MethodsStructured national telephone survey of ambulatory care physicians, four thematic blocks with 21 questions (5 point Likert scale). 511 office-based gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 16 publications
7
28
2
5
Order By: Relevance
“…While initial studies are available for general practitioners and internal medicine specialists [20,21,22], our study is the first evaluation of a clinical practice guideline in Neurology in Germany. The focus was on collecting initial experience on the awareness of the guideline on PD and related disorders in everyday medical practice 3 years after its first dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…While initial studies are available for general practitioners and internal medicine specialists [20,21,22], our study is the first evaluation of a clinical practice guideline in Neurology in Germany. The focus was on collecting initial experience on the awareness of the guideline on PD and related disorders in everyday medical practice 3 years after its first dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a large group of GPs is critical and opposed to utilization of clinical practice guidelines in daily practice as well as to the concept of EBM in general (Butzlaff et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…De todos modos, su utilidad práctica es controvertida. En encuestas realizadas a médicos de AP en Alemania, hasta un 33% de los facultativos rechazaba su aplicación en el cuidado de pacientes 19 . En un estudio con grupos focales en médicos de AP en nuestro medio, los facultativos muestran una actitud positiva hacia la MBE pero la aplicación en la práctica diaria es escasa, especialmente en relación con la falta de tiempo y la presión asistencial 20 .…”
Section: Discussionunclassified